2016
DOI: 10.1111/gfs.12231
|View full text |Cite
|
Sign up to set email alerts
|

Survival and recovery of tall fescue genotypes: association with root characteristics and drought tolerance

Abstract: Identification and selection of plant genotypes with survival, recovery and sustainable performance during drought periods is one of the main objectives of plant improvement for arid and semi-arid regions. This study aimed to evaluate root traits and recovery of tall fescue genotypes after a period of drought stress. A total of twenty four tall fescue genotypes were selected from a wide polycross population and assessed for field drought tolerance based on stress tolerance index (STI) and recovery during 2010-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Festuca arundinacea Schreb.) genotypes (Table S1) were selected from our previous materials based on productivity related traits according to the results of previous studies (Majidi et al., 2009; Pirnajmedin et al., 2016). The genotypes were clonally propagated in a greenhouse and then transferred to the field in March 2015.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Festuca arundinacea Schreb.) genotypes (Table S1) were selected from our previous materials based on productivity related traits according to the results of previous studies (Majidi et al., 2009; Pirnajmedin et al., 2016). The genotypes were clonally propagated in a greenhouse and then transferred to the field in March 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Pirnajmedin et al. (2016) reported that selection based on combining a stress tolerance index (STI), recovery and an extensive root system might improve the drought tolerance of tall fescue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like phenotypes and plasticity, recovery ability differs among genotypes in other grasses (e.g. Cui et al., 2015; Hawkes & Kiniry, 2018; Pirnajmedin et al., 2016), but comparisons are rarely made among coexisting genotypes of a single population, and may not reflect strategies occurring in local‐scale communities versus among populations. For example, Andropogon gerardii genotypes differ in recovery of gene expression and physiology following re‐watering (Avolio et al., 2018; Avolio & Smith, 2013b), but it is unclear if these findings apply to productivity and growth‐related phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…() found that water stress reduced root biomass, specific root length (RL), root tissue density and root dry matter content and increased root diameter in some forage grasses. In tall fescue ( Festuca arundinacea ), significant reduction in RL, root area (RA), root volume, root weight and root dry matter percentage is reported under water stress conditions (Pirnajmedin, Majidi, & Gheysari, , ). Wang and Bughrara () reported that drought stress significantly reduced root biomass and RL of several forage grasses.…”
Section: Introductionmentioning
confidence: 99%